Effect of Nutrition during Pregnancy on Calf Birth Weights and Viability and Fetal Membrane Expulsion in Dairy Cattle - ZHANG, Wen-Chang; MORIYOSHI, Masaharu; NAKADA, Ken; KIDA, Katsuya; NAKAO, Toshihiko (Journal of Reproduction and Development, 2002)
The objectives of this study were to show changes of blood parameters for nutrition during pregnancy and to examine the relationships between the blood parameters and calf birth weights, calf viability, time required for expulsion of fetal membrane, and the fetal membrane weights. Forty-one Holstein Friesian pregnant cows were used. The duration of the dry period was 74 ± 2 (SEM) days. The average milk yield (4% FCM) per cow per lactation for 305 days was 9,795 ± 146 kg. Mean gestation length, body weight of cows at parturition, and cotyledonary weight were 283.7 ± 0.5 days, 761 ± 11 kg, and 1562 ± 33g, respectively. Mean birth weights were 47.4 ± 1.1 kg for female, and 49.8 ± 0.8 kg for male calves. Of the 41 cows, 10 had weak calves and 13 had retained fetal membranes (RFM). No significant effects of parity, bull, lactation length, milk yield, gestation length, cows' body weights, and gender of calves on the cotyledonary and calf birth weights, incidences of neonatal weakness and RFM were shown. Cows showing low plasma glucose and TP concentrations in mid and late lactation periods had lower calf birth weights and cotyledonary weights, and a higher incidence of neonatal weakness. Likewise, cows with low glucose, cholesterol and Ca concentrations in plasma during the late dry period had a higher incidence of RFM. The results indicate that low intake of energy and protein during late lactation and early dry periods adversely affects feto-placental development, leading to neonatal weakness and RFM. Low intake of energy and Ca during the dry period may also cause RFM.